The Silent Church - Plantak, Zdravko. author. aut Link
XIII, 271 p.
Keywords: The relationship between the Adventist church and society at large has always been ambiguous. One reason for this has been the church's inarticulate social ethics. While the church upheld the concept of human dignity, promoted religious liberty and sided with the poor, nationalism and racism developed among its members. Women in the church were also unfairly treated. Zdravko Plantak confronts this problem head-on. He begins by looking at the church's history, theology and ethics in order to discover reasons for the inconsistencies in its approach to human rights, and then moves on to propose a more comprehensive approach to its social ethics.